2006
DOI: 10.1210/en.2005-1017
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-15 in the Zebrafish Ovary: Complementary Deoxyribonucleic Acid Cloning, Genomic Organization, Tissue Distribution, and Role in Oocyte Maturation

Abstract: Bone morphogenetic protein-15 (BMP-15) is a member of the TGFbeta family known to regulate ovarian functions in mammals. The structure and function of BMP-15 in lower vertebrates are less known. In this study, we cloned the zebrafish BMP-15 (zfBMP-15) cDNA and depicted its genomic organization. The zfBMP-15 cDNA encodes a protein of 384 amino acids. The mature protein has 46-51% sequence identities to fugu, chicken, and mammalian BMP-15. It also shares 38-46% homology with growth and differentiation factor-9 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 51 publications
4
61
1
Order By: Relevance
“…In fact, previous studies on zebrafish have described how treatment with recombinant human TGFB1 inhibits oocyte maturation reducing Lh activity by decreasing lhcgr and cbr1l mRNA levels, and have shown decreased basal and hCG-induced paqr8 mRNA levels in zebrafish follicles (Kohli et al 2005). Similar results have also been obtained with recombinant human BMP15, which also reduced hCG-induced oocyte maturation (Clelland et al 2006). Moreover, the knockdown of bmp15 in oocytes, by antisense oligonucleotides, increased paqr8 expression (Tan et al 2009), and the inhibition of bmp15 expression or function in class IIIa follicles has been found to induce their sensitivity to MIH (Clelland et al 2006(Clelland et al , 2007.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In fact, previous studies on zebrafish have described how treatment with recombinant human TGFB1 inhibits oocyte maturation reducing Lh activity by decreasing lhcgr and cbr1l mRNA levels, and have shown decreased basal and hCG-induced paqr8 mRNA levels in zebrafish follicles (Kohli et al 2005). Similar results have also been obtained with recombinant human BMP15, which also reduced hCG-induced oocyte maturation (Clelland et al 2006). Moreover, the knockdown of bmp15 in oocytes, by antisense oligonucleotides, increased paqr8 expression (Tan et al 2009), and the inhibition of bmp15 expression or function in class IIIa follicles has been found to induce their sensitivity to MIH (Clelland et al 2006(Clelland et al , 2007.…”
Section: Discussionsupporting
confidence: 77%
“…In vitro maturation assays were conducted as described previously (Clelland et al 2006). The ovaries were teased into separate follicles using transfer pipettes (Samco Scientific Corp., San Fernando, CA, USA) without trypsinization.…”
Section: Follicles In Vitro Maturation Assaymentioning
confidence: 99%
“…These data are not in agreement with some studies that report an involvement of BMP-15 in oocyte maturation and cumulus expansion in mice (Yoshino et al 2006) and pigs (Li et al 2008). However, recent studies in zebrafish have demonstrated that BMP-15 exerts a physiological role to inhibit oocyte maturation (Clelland et al 2006(Clelland et al , 2007Peng et al 2009). In this species, BMP-15 has shown the ability to prevent premature oocyte maturation, which has been considered important for the maintenance of oocyte quality and subsequent ovulation and fertilization (Peng et al 2009).…”
Section: Discussioncontrasting
confidence: 76%
“…BMP15 is produced by oocytes and plays important roles within the ovary, such as promoting early folliculogenesis and enhancing cumulus cell expansion (Peng et al, 2009). Previous reports have revealed that BMP15 prevented precocious oocyte maturation in zebrafish to maintain oocyte quality (Clelland et al, 2006;Peng et al, 2009). In addition, c-kit (also known as CD117) is a member of the tyrosine kinase and the receptor of the SCF.…”
Section: Discussionmentioning
confidence: 99%